Parkinson's Disease in Pregnancy: A Case Report and Review of the Literature - Olivola, Sara; Xodo, Serena; Olivola, Enrica; Cecchini, Fabiana; Londero, Ambrogio Pietro; Driul, Lorenza (Frontiers in Neurology, 2020)
Background: Pregnancy in Parkinson’s disease is a rare occurrence and to date clinical experience with its management is rather limited. In clinical practice, doubts concern mainly the impact of PD on gestation, labor and delivery as well as the safety of dopaminergic drugs. Case and review of the literature: We report the case of a 40-years old woman with an 8-year history of PD. In the first trimester of her pregnancy, her motor status was similar to the pre-conceptional period. In gestation week 16 her motor status dramatically worsened and she complained of predictable “off” periods in the afternoon. For this reason her dose of L-dopa/Carbidopa was increase up to 500/125 mg per day. At 39 gestational weeks she gave birth to a healthy girl with an Apgar score of 9 by an uncomplicated caesarean delivery. The child was not breast fed to avoid exposure to antiparkinsonian drugs. The L-Dopa/Carbidopa dosage remained constant during the postpartum period. We performed a systematic review of the literature using Ovid Medline, Scopus, and PubMed (including Cochrane database). We used the search terms “Parkinson disease” AND “pregnancy”. We identified 20 studies of PD in pregnancy with a total of 37 pregnant women with PD. The most important available data concern the safety of L-dopa therapy during pregnancy. There seems to be some risk of worsening of the condition or upcoming of new PD symptoms during or shortly after pregnancy. Conclusion: More data concerning the safety of antiparkinsonian drugs in PD treatment, as well as the effect of pregnancy on parkinsonian symptoms are needed. According to the current state of the art, L-dopa therapy should be considered preferable to other drugs during pregnancy.